Multi-agent class timetabling for higher educational institutions using prometheus platform - Angelita D. Guia; Melvin A. Ballera (Institute of Advanced Engineering and Science, 2021)
A in a university setting, class scheduling is vital for teaching and learning process. Academic institutions rely on time tables in their day to day activities. University Course Timeframe problem can be resolved by using multi-agent systems-based method which may increase the independence of each department's class scheduling, adaptability in a distributed environment and prevents conflicts between events or resources, and unforeseen allocation through intervention between agents in a dispersed environment. Class timing is performed manually in most of the higher educational institutions, which is a very challenging and time-consuming process. The main objective of the study is to build a multi-agent class timing system that automates the process of class scheduling of higher education institutions (HEIs) using the Prometheus methodology. The implementation of the Prometheus approach in the development of a multi-agent framework has resulted in a complete and comprehensive system covering all phases of software development as applied to the agent systems.